Glycemic Control in Adolescent Girls with Type 1 Diabetes Mellitus - Yomna Shaalan; Nora ElSaid Badawi; Aliaa Soliman; Abdelkarim Kamel; Marise Abdou (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Background: Optimal glycemic control is essential during type 1 diabetes (T1D) management to minimize the occurrence of both short and long term complications. Many factors might influence diabetes control including puberty which is a challenging period. Aim of the work: To assess the effect of puberty on glycemic control in adolescent females with T1D and to compare glucose levels, insulin demand and carbohydrate intake in the week of menstruation to those in the luteal phase. Methods: This cross-sectional, pilot study took place in the Diabetes, Endocrine and Metabolism Pediatric Unit, Cairo University Children's Hospital, Egypt. It included 30 prepubertal Tanner stage 1 girls (Group-1) and 30 full pubertal girls Tanner stage 5 (Group 2) with regular menstruation were included in the study. Mean blood glucose levels, insulin doses and glycated hemoglobin(HbA1C) (average of the last 4 readings over 1 year) were compared. Results: Ages of enrolled girls ranged from 10-15 years (group 1: mean age ± SD=11.67±1.33; group 2: 13.93±.0.94; p < 0.001 ) with T1D durations of 5.12-5.42 years. Mean HbA1c and insulin doses were similar in both pubertal and prepubertal girls after adjusting data for BMI SDS and participation in exercise (p=0.164 and 0.157 respectively). Mean blood glucose levels, insulin doses and carbohydrate intake were significantly higher (by 8%, 18% and 7.5% respectively) during menstruation (early follicular) than in the luteal phase (p < 0.001). Conclusion: Glycemic control in pubertal females with T1D was challenged by the higher BMI, lack of activity and growth spurt that characterize this stage of development. Contrary to some other studies, among our studied cohort glycemic control also exhibited deterioration in the early follicular phase that was associated with greater carbohydrate consumption compared to the luteal phase.